A Cooperative Cache Management Scheme for IEEE802.15.4 based Wireless Sensor Networks - Piyush Charan; Tahsin Usmani; Rajeev Paulus; Syed Hasan Saeed (Institute of Advanced Engineering and Science, 2018)
Wireless Sensor Networks (WSNs) based on the IEEE 802.15.4 MAC and PHY layer standards is a recent trend in the market. It has gained tremendous attention due to its low energy consumption characteristics and low data rates. However, for larger networks minimizing energy consumption is still an issue because of the dissemination of large overheads throughout the network. This consumption of energy can be reduced by incorporating a novel cooperative caching scheme to minimize overheads and to serve data with minimal latency and thereby reduce the energy consumption. This paper explores the possibilities to enhance the energy efficiency by incorporating a cooperative caching strategy.